Programmed death 1 blockade, an Achilles heel for MMR-deficient tumors?. Issue 1 (December 2015) - Lin, Andy; Lin, Edward
Abstract Program death receptor-1 (PD-1) is upregulated in many tumors and in tumor microenvironment, and PD-1 blockade has led to remarkable immune-based anti-tumor responses in across many tumor types. Pembrolizumab, an anti-programmed death 1 checkpoint inhibitor, resulted in a high rate of immune response in 41 patients with previously treated mismatch repair (MMR)-deficient tumor including colorectal cancer but not in MMR-stable tumor with expectant toxicities. Both immune-based progression-free and overall survival are quite promising and correlate with high mutation loads in the tumor. MMR-deficient tumors made up not an insignificant proportion of GI and GU cancers and are found mostly in younger patients who had better prognosis than MMR-stable tumors. However, MMR-deficient tumors do not respond to cytotoxic chemotherapy as these agents may require intact DNA mismatch repair to be effective. MMR deficiency occurred as a result of mutations in defined DNA repair complex mutations or epigenetics modifications and gene upstream of DNA repair complex. PD-1 blockade represents our first successful shot at one of the Achilles heels of this MMR-deficient tumor goliath. Only coordinated attack on all of its Achilles heels and healing mechanisms can this tumor Goliath be brought down to its knees.